Criminal Liability of Indonesian National Army (Tni) Members for the Crime of Abusing Class I Narcotics for Themselves (Study of Dilmiltama Decision 3-K/Pmu/Bdg/Au/III/2019) - Nadeak, Linson; Arifullah, Achmad (UNISSULA Semarang, 2025)
This thesis examines the criminal liability of Indonesian National Armed Forces (TNI) members involved in the abuse of Class I narcotics for personal use, with a case study of Decision DILMILTAMA 3-K/PMU/BDG/AU/III/2019. The increasing issue of narcotics abuse, including among state officials and law enforcement personnel, highlights a critical national problem that threatens the nation's future. This research aims to analyze the application of criminal sanctions against TNI members who commit narcotics abuse and to scrutinize the legal considerations of military courts in handing down verdicts for such cases. Utilizing a normative juridical research method with an analytical descriptive approach, the study investigates primary and secondary legal materials, including laws, legal principles, and judicial decisions. The case under review, Decision DILMILTAMA 3-K/PMU/BDG/AU/III/2019, involved defendant X, who was convicted of using Class I narcotics for personal consumption. The results of this study indicate that members of the Indonesian National Armed Forces (TNI) who are proven to have abused Class I narcotics for personal use can still be held fully criminally liable, as specified in Law Number 35 of 2009 on Narcotics and relevant military regulations. In this case, the defendant, Muhammad Akhyar, was sentenced to imprisonment and was also subjected to dishonorable discharge (PTDH) as a form of both criminal and administrative accountability.